Equations of the Sum of Shear Connector on the Double Shear Connection Strength using Different Connector Materials - Dwi Joko Priyono; Surjono Surjokusumo; Yusuf S. Hadi; Naresworo Nugroho (Wood Research Journal, 2012)
Mangium wood from the timber estate have been developed continuously in an effort to reach the fulfilling of wood fiber and construction material needs to replace role of timber from the natural forests which has been decreased. Timber connection requires a connector such as bolt that can distribute both the load of wood to wood and the compression or tensile stress through all the connections. Bearing slip is a connector that is inserted into a hole in the wood, which bears pressure and shear. Bolted connection is the most commonly used because it is easy to apply, even though it is less efficient due to the shear forces will be retained by the bolts and wood only on the cross-sectional area of the bolt. This research trying to find the equations of the sum of  bearing slip connector to the strength of double shear connection  which composed of 17 years old mangium. The connector was made from  different materials that consisted of the same mangium, compressed mangium, ironwood and steel. The bearing slip connector consisted of two forms (dowel and rectangular) and arranged on one until three pairs of connector. The size and placement of the double-shear component based on Anonymous (2002), each form of the sample was made in 4 replications and all of them have been tested using a 35-ton Baldwin UTM. The result showed that the rectangular steel bearing slip connector has the highest equation (y = 5322e0.329x ) meanwhile the lowest equation was the ironwood materials (y = 3164e0.405x ). All of equations give high correlations ( R2 between 0.743 to 0.947).  Bearing slip connector can improve the ability of the connection in load-bearing. Densified of mangium able to raise the connection system's ability however not significantly, both in strength and displacement. Ironwood connector are not well used as a retaining shear pin because of easy to split and significantly much below in capacity than mangium wood. Steel connector resulted the higher load-bearing significantly than mangium and ironwood. Dowel do not differ in terms of strength as compared with rectangle, and each additional number of connector producing an increase in load-bearing ability significantly. Observation on the displacement value shows that for the value which applied usually in Indonesia reach the strength ratio (SR) as 92.21% to the proportion limit and 44.91% to the maximum load. This value was in below position of the US standard  (24.17 and 11.77%) and of the Australian standard (51.46 and 25.06%) to the proportional limit and maximum load respectively. Displacement achievement at the proportional limit varies from 1.1 to 2.2 mm, so that the minimum requirement of 1.5 mm displacement is not fulfilled by some treatments, however all of the connection system have passed the 1 mm displacement.